IMPROVING STUDENTSâ ABILITY IN WRITING NARRATIVE TEXT THROUGH ACCELERATED LEARNING APPROACH ATMADRASAH ALIYAH TAMAN PENDIDIKAN ISLAM MEDAN - Saleh, Anwar; Sihombing, Lince; Santoso, Didik (TABULARASA, 2015)
The objective of the study was to find out how accelerated learning approach can be used to improve the writing ability of students. The study was collaborative classroom action. This study was conducted in two cycles of which each cycle consisted of three meetings. The data of the study were gathered through observation checklist, field notes, and writing test. The subjects were 42 second year students of 2015/2016 MA Taman Pendidikan Islam. The finding of the study indicated that the use of Accelerated Learning approach successfully improved studentsâ writing narrative text from 49.6 in the preliminary study, and 60.2 in the first cycle to 70.2 in the second cycle. It indicated that Accelerated Learning approach was effective in enhancing the studentsâ motivation and participation. Most students (92.60%) were involved actively in writing. It is suggested that English teachers apply Accelerated Learning approach since it is beneficial not only to improve the studentsâ narrative text writing but also to motivate the students to write and to work together to describe the event in the picture as well as to encourage students actively participating in writing narrative text.